Carcass and meat quality of Thai native cattle fattened on Guinea grass (Panicum maxima) or Guinea grass-legume (Stylosanthes guianensis) pastures - S. Jaturasitha (2018)
Carcass and meat quality of Thai native cattle, fattened for 2 years on Guinea grass (Panicum maxima) and Guinea grass-legume (Stylosanthes guianensis) pastures, were investigated in twelve 3-years old males. Groups had similar carcass quality except for kidney fat percentage (higher in cattle of the grass-legume group). This group also had a lighter meat (Longissimus dorsi, Infraspinatus) than the grass-only fed cattle. Shear force was generally at the borderline to tender meat, and was unaffected by treatment as were other texture-related properties except muscle fibre diameter. Meat of the grass-legume group was perceived less juicy (P < 0.05) but more tender (P < 0.1). The meat of the grass-legume-fed cattle also had more intramuscular fat (4.3% vs. 3.4%) and a slightly less favourable n-6:n-3 fatty acid ratio (2.2 vs. 2.0). In conclusion, the mostly weak differences in carcass and meat quality did not clearly favour one of the grazing systems. © 2008 Elsevier Ltd. All rights reserved.